PENINGKATAN KETERAMPILAN MENULIS KREATIF BERMUATAN PENDIDIKAN BUDI PEKERTI PADA GURU-GURU SEKOLAH DASAR MELALUI HYBRID LEARNING - Winarni, Retno; Slamet, St Y; Poerwanti, Jenny IS; Sriyanto, Muhammad Ismail; Yulisetiani, Septi; Syawaludin, Ahmad (JURNAL WIDYA LAKSANA, 2022)
This service activity aims to improve creative writing skills with character education for elementary school teachers through face-to-face and virtual training. The participatory method was used in this training to stimulate teachers to be active in practicing poetry writing both in theory and practice. Face-to-face meetings were held twice for theoretical training, while virtual meetings were held for practical training in writing poetry and presenting it. Based on the results of scoring the ability to write poetry in the posttest session, the classical ability in writing poetry was 84.90%, where at the pretest stage it was 70.79%. The results show that poetry writing training containing character education through a mixed face-to-face and virtual method (Hybrid Learning) is able to improve the ability of elementary school teachers in writing creative poetry types. The improvement in the poetry writing skills of the participants was seen in all aspects of writing poetry, including themes and meanings, the power of imagination, accuracy of diction, and the message.